Jobs and Growth : Supporting the European Recovery - Schindler, Martin (International Monetary Fund, 2014)
Collection of research providing guideposts toward offering opportunities for stronger and better-balanced growth and employment in postcrisis Europe.
Keywords: Labor market -- Europe.; Structural adjustment (Economic policy) -- Europe.; Economic development -- Europe.; Marché du travail -- Europe.; Ajustement structurel (Économie) -- Europe.; Développement économique -- Europe.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Economic development; Labor market; Structural adjustment (Economic policy); Europe; Arbeitsmarktpolitik; Europa; Arbeitsmarkt.; Wirtschaftliche Anpassung.; Arbeitsmarktpolitik.; Wirtschaftspolitik.; Wirtschaftswachstum.; Europa.